The latin Renovatio of Byzantium the empire of Constantinople (1204 - 1228) - Tricht, Filip van; Tricht, Filip van (Leiden [u.a.] Brill, 2011)
Prologue -- The constitutional treaties of 1204-1205 : the Latin restructuring of Byzantium -- The imperial ideology -- The imperial quarter -- Imperial authority within the empire in its entirety -- The central elite -- Religion, church, and empire -- The Byzantine space -- The Latin Orient
Prologue -- The constitutional treaties of 1204-1205 : the Latin restructuring of Byzantium -- The imperial ideology -- The imperial quarter -- Imperial authority within the empire in its entirety -- The central elite -- Religion, church, and empire -- The Byzantine space -- The Latin Orient.
Includes bibliographical references and index
Teilw. zugl.: Ghent, Univ., Diss., 2004
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Crusades -- Fourth, 1202-1204; Imperialism -- Social aspects -- Byzantine Empire -- History; Social Change -- Byzantine Empire -- History; Istanbul (Turkey) -- History -- To 1453; Istanbul (Turkey) -- Politics and government; Istanbul (Turkey) -- Social conditions; Byzantine Empire -- History -- 1081-1453; Byzantine Empire -- Politics and government; Latin Empire, 1204-1261; Istanbul (Turkey) -- History -- Siege, 1203-1204; Crusades -- Fourth, 1202-1204; Byzantine Empire -- History -- 1081-1453; Byzantine Empire -- Politics and government; Imperialism -- Social aspects -- Byzantine Empire; Social change -- Byzantine Empire; Latin Empire, 1204-1261; Istanbul (Turkey) -- History -- Siege, 1203-1204; Istanbul (Turkey) -- History -- To 1453; Istanbul (Turkey) -- Politics and government; Istanbul (Turkey) -- Social conditions; Hochschulschrift